Cingulate sulcus sign: a descriptive analysis in a cerebral small vessel disease population - Li, Weishuai; Su, Chang; Wang, Zhihan; Xu, Xiaoxuan; Zheng, Dongming (Frontiers in Aging Neuroscience, 2024)
The cingulate sulcus sign (CSS) has been observed in patients with idiopathic normal pressure hydrocephalus (iNPH), suggesting potential disruptions in cerebrospinal fluid circulation and compromised glymphatic system. Although there are similarities in the underlying mechanisms between cerebral small vessel disease (CSVD) and iNPH, the relationship between CSS and CSVD remains unclear. This study aimed to investigate the prevalence and potential mechanisms of CSS in patients with CSVD Methods: Data from patients diagnosed with CSVD at Shengjing Hospital of China Medical University between January 2020 and October 2022 were retrospectively collected, including general information, global cognitive function (assessed by measuring Mini-Mental State Examination (MMSE)), and four CSVD magnetic resonance imaging (MRI) markers ((white matter hyperintensity (WMH), cerebral microbleeds (CMBs), lacunes, and enlarged perivascular spaces (EPVS)), CSS and the Evan's index (EI)Results: A total of 308 patients were included, and CSS was detected in 80 patients (26%).Univariate analysis revealed that MMSE scores in the CSS group were significantly lower compared to the non-CSS group (p < 0.001). Multivariable analysis showed an independent correlation between CSS and the presence of lacunes (odds ratio [OR] 0.358, 95% confidence interval [CI] 0.193-0.663, p=0.001),presence of lobar dominant CMBs (OR 2.683, p=0.003), periventricular WMH Fazekas score (OR 1.693, p=0.01) ,and EI (OR 1.276, p＜0.001) Conclusion: This preliminary study showed that CSS can be observed in some patients with CSVD. The presence of CSS may represent different mechanisms of CSVD pathogenesis and reflect differences in the degree of cerebrospinal fluid (CSF)/interstitial fluid (ISF) stasis.